‘El Diego de la gente’: the most human of the football Gods - Rial, Carmen (Eracle. Journal of Sport and Social Sciences, 2022)
Football and religion maintain a beneficial association and it would not be an exaggeration to say that contemporary football presents the most watched religious performances in the world (Rial, 2012). Some authors even compare football to a new religion. In the multisite ethnographic research about football that I have conducted in more than 15 countries since 2003, I found expressions of devotion to various celebrity players who are treated as “saints” and “messiahs” – yet none with the intensity of Maradona, who has his own Church in Argentina, chapels in the streets of Naples, and there was passionate commotion at his wake. Inquiring into the relationship between football and religion, the article explores the characteristics of the star Maradona, who is closer to the ambiguous figure of Exú than other more Apollonian football “deities”. It examines why Maradona deserves such worship and how this banal religiosity echoes among football fans. Cheering for Maradona can be seen as a weapon of the weak to beat puissant, at least imaginarily.